Strategi Komunikasi Pemasaran Rumah Zakat Tahun 2022 - Nenie Sofiyawati (UIN Antasari Banjarmasin, 2022)
The Covid-19 pandemic has prompted changes in market behavior in all sectors of life, including paying zakat. Donors mostly use online and digital media to fulfill their obligation to pay zakat. Rumah Zakat takes advantage of this moment to maximize its marketing communications so that it becomes an international philanthropic institution based on professional empowerment. This study describes the implementation of Rumah Zakat's marketing communication strategy in 2022 using Philip Kotler's theory of effective marketing communication and applies a qualitative description method of literature from various relevant references. The results of the study show that the marketing communication strategy of Rumah Zakat in 2022 is as follows: the target market is donors from individuals, corporations, and communities; promotional objectives meet the needs of donor readiness to donate until decision making; message design using the rationality of zakat, encouraging zakat, doing good and sharing happiness through the hashtag #saatnyaTumbuhBersama; the format of the message conveyed is very strong, easy to understand and fun; communication channels using private and non-private channels; sources of messages from internal and external with the dominance of young people.